Comparing Conventional Bank Credit Vis A Vis Shariah Bank Musharakah: Experimental Economic Approach - Muhamad Abduh; Yulizar Djamaluddin Sanrego (Tazkia Islamic Finance and Business Review, 2008)
Central Bank of Indonesia with dual banking system – i.e Shariah and Conventional Bank – keep on developing system that considered as an answer to generate the national economic growth. One of the banking activities that emphasized by the Central Bank of Indonesia is fund distribution through either conventional bank credit or shariah bank fi nancing. Having the Experimental Economic Approach based on Induced Value Theory and employing ANOVA, this paper found that shariah bank musharakah fi nancing system would come up with higher profi t opportunity compare to conventional credit system. One main reason is that musharakah fi nancing in shariah bank applies profi t and lost sharing (PLS) scheme so that will not be a burden to the customer when he fi nd low profi t.Keywords: Credit Loan, Musharakah Financing, Induced Value Theory, Experimental Economic Approach, Analysis of Variance (ANOVA).